Prooxidant capacity of phenolic acids defines antioxidant potential - Mu, Kaiwen; Yao, Yufeng; Wang, Danni; Kitts, David D. (Biochimica et biophysica acta. General subjects, 2023)
Phenolic acids derived from vegetables, fruits and beverages are considered abundant sources of natural antioxidants consumed in the human diet. In addition to having well-known antioxidant activity, phenolic acids also exhibit pro-oxidant activity under selected conditions. We hypothesized that the availability of extracellular H2O2 derived from phenolic acid autoxidation will diffuse across cell membranes to participate as a messenger molecule to activate intracellular redox signaling in response to oxidative stress. We report on the relative activity of structurally different phenolic acids to generate specific changes in the extracellular - intracellular H2O2 flux that induces intracellular redox signaling corresponding to a function to reduce intracellular oxidative stress. HyPer-3 methodology was used to measure increases in intracellular H2O2 in differentiated Caco-2 intestinal cells in response to phenolic acid autoxidation and changes in extracellular H2O2 production. The potential for different phenolic acids to autoxidize and generate H2O2 was dependent on the structure and concentration of phenolic acid. Activation of nuclear factor erythroid 2-related factor (Nrf2) cell signaling was enhanced (p < 0.05) by phenolic acid induced H2O2 production, and mitigated when present along with catalase (p < 0.05), or, alternatively by blocking aquaporin 3 (AQP3) function (p < 0.05) using DFP00173 as the AQP3 inhibitor. The relative capacity of phenolic acids to generate H2O2 via autoxidation was structure specific and corresponded to the level of Nrf2 cell signaling in differentiated Caco-2 epithelial cells. The Nrf2-Keap1 response paralleled the extent of reduced oxidative stress observed in differentiated Caco-2 cells determined by dichloro-dihydro-fluorescein diacetate (DCFH-DA) assay. [Display omitted] •This research paper highlighted the specific physicochemical property of phenolic acids that explain generation of H2O2 in culture conditions.•The HyPer-3 enabled characterization of phenolic acid-specific derived H2O2 in intracellular space.•Phenolic acid-derived changes in intracellular H2O2 activates Nrf-2 cell signaling and potential increased cell eustress.•Aquaporins also indirectly control activation of Nrf2 cell signaling.